STRATEGI TIM MEDIA DALAM UPAYA PROMOSI LEMBAGA PAUD - Aulia, Ana; Fitri, Nur Lailatul; Novitasari, Nurul; Masruroh, Farhatin (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to determine the strategy of the media team in an effort to promote the institution and the obstacles it faces. This research uses a qualitative approach with a descriptive approach. This research was conducted at TK Islam Plus Insan Kamil Tuban. This research uses observation, interview, and documentation methods. In this study there were 3 informants including: the head of the school, the deputy head of the school, and the head of the institutional media team division. The results of the study show that the strategies used by the media team in promoting the institution are carried out online and offline. Online is done by: 1) creating content planner calendars, 2) creating social media accounts, 3) creating content, 4) uploading content on social media, 5) evaluation. The offline promotion strategies include: 1) collaborating with various agencies, 2) sharing and caring, 3) inviting influential people, 4) teacher branding and work branding. The obstacles faced were: 1) internet network disruption, 2) delays in content creation, 3) some media teams required more intense training related to making promotional media, 4) evaluation.